2019
DOI: 10.3390/f10110987
|View full text |Cite
|
Sign up to set email alerts
|

Storage and Climatic Controlling Factors of Litter Standing Crop Carbon in the Shrublands of the Tibetan Plateau

Abstract: Litter is an important component of terrestrial ecosystems and plays a significant role in carbon cycles. Quantifying regional-scale patterns of litter standing crop distribution will improve our understanding of the mechanisms of the terrestrial carbon cycle, and thus enable accurate predictions of the responses of the terrestrial carbon cycle to future climate change. In this study, we aimed to estimate the storage and climatic controlling factors of litter standing crop carbon in the Tibetan Plateau shrubla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…The aboveground biomass promotes more litter input and positively impacts the standing stock of litter. Due to the stimulation of more aboveground biomass input, soil organic matter also positively impacts the standing stock of litter [4]. The results show that all nutrients in litter are significantly positively correlated with soil.…”
Section: Introductionmentioning
confidence: 94%
“…The aboveground biomass promotes more litter input and positively impacts the standing stock of litter. Due to the stimulation of more aboveground biomass input, soil organic matter also positively impacts the standing stock of litter [4]. The results show that all nutrients in litter are significantly positively correlated with soil.…”
Section: Introductionmentioning
confidence: 94%
“…STN was found to show a significant increasing trend with increasing biomass, whereas the relationship between STP and biomass was minor (Figure 2). In general, more biomass tends to cause a greater accumulation of forest litter (Nie et al, 2019), and this litter and plant residue contribute to increase in soil N input (Liu X. et al, 2010;Liang et al, 2019). As a result, increasing biomass triggered a positive relationship between STN and biomass in alpine wetland and alpine meadow in the Three Rivers Source Region on the Qinghai-Tibetan Plateau.…”
Section: Effects Of Vegetation Properties On Soil Total Nitrogen and ...mentioning
confidence: 99%
“…Studies have shown that litter layer decomposition accounts for about 5% to 45% of the total soil CO 2 emission [15,52]. In order to reveal the mechanism of continuous mineralization and transformation of carbon in litter, Rubino et al found that 2/3 of the carbon in the litter enters the soil in the form of soluble carbon or debris and 1/3 enters the atmosphere in the form of CO 2 by using 13 C isotope tracing technology [16]. The addition of litter had a significant effect on the rate of soil CO 2 release, and also significantly increased the contents of soil dissolved organic carbon and microbial biomass carbon [53].…”
Section: Influence Of Litter On Soil Inorganic Carbonmentioning
confidence: 99%
“…Litter is the main source of topsoil organic matter, and plays an important role in changing soil properties, soil bulk density and porosity [12]. Quantifying the regional scale model of the current stock distribution of litter and studying the decomposition process of litter will help to improve the understanding of the mechanism of terrestrial carbon cycle and promote the accurate prediction of the response of terrestrial carbon cycle to future climate change [13].…”
Section: Introductionmentioning
confidence: 99%